FAKTOR-FAKTOR YANG MEMPENGARUHI COST OF CAPITAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2020 - Mitha Christina Ginting (JURNAL MANAJEMEN, 2021)
This research aims to find out the factors that affect the cost of capital in manufacturing companies listed on the Indonesia stock exchange for the period 2017 - 2020. This study is motivated by inconsistency in the results of previous studies on each variable independent of the dependent variable. The survey covered all manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2020, for a total of 180 companies. The study used purposive sampling techniques obtained by 124 samples that met the criteria. This research is quantitative research using the type and source of data in the form of secondary data obtained from www.idx.co.id. The data analysis methods used in this study are descriptive statistical analysis, classical assumption test, and multiple linear regression analysis.  The results showed that, (1) information asymmetry had a significant positive effect on the cost of capital, (2) profit management had a positive and significant effect on the cost of capital, (3) the size of the company had no significant effect on the cost of capital; (4) voluntary disclosure had a significant positive effect on the cost of capital;  and (5) simultaneous information asymmetry, profit management, company size and voluntary disclosure have a significant effect on the cost of capital.